The Blair Witch Project [videorecording (DVD)] - Myrick, Daniel, 1962-; Myrick, Daniel, 1962-; Myrick, Daniel, 1962-; Sánchez, Eduardo; Sánchez, Eduardo; Sánchez, Eduardo; Donahue, Heather, 1973-; Williams, Michael, 1973-; Leonard, Joshua (Artisan Entertainment, 1999)
Three student filmmakers set out into the forest to film a documentary on a legend known as The Blair Witch. As they become lost in the woods, an unseen evil begins to stalk and harass them. They soon realize that what they are filming is not a legend, but their own descent into a horrifying encounter with the supernatural.